Who are the most influential criminologists in the english-speaking world? - Cohn, Ellen G. (The British journal of criminology, 1994)
We aim to investigate the most influential criminologisls in the English-speaking world during the period 1986 to 1990. While cautioning the reader that citations and influence are not perfectly correlated, we focus on citations in four major journals. The most-cited criminologists in the British Journal of Criminology, Criminology, the Canadian Journal of Criminology, and the Australian and Mew Zealand Journal of Criminology were determined. A combined score showed that four American criminologists were particularly influential in all major countries: Marvin E. Wolfgang, Alfred Blumstein, James Q. Wilson, and Michael J. Hindelang. This pre-eminence was connected with longitudinal research on criminal careers Wolfgang, Blumstein, measuring crime Wolfgang, Blumstein, Hindelang, correlates of crime Hindelang, Wilson, and public policy discussions Wilson. While realizing the limitations of an analysis based only on four journals, we showed that adding a fifth major journal Justice Quarterly did not substantially change our conclusions. Generally, the most influential criminologists in the United States also tended to be influential everywhere else, whereas the most influential criminologists in other countries might be influential nowhere else